A flow-injection-ICP system sequential multielemental analysis with simultaneously mercury(II) preconcentration step - Zara, L. F.; Rocha, J. C.; Milani, M. R.; Rosa, André Henrique [UNESP]; dos Santos, A.; Serudo, R. L. (Marcel Dekker Inc, 2003)
A flow-injection system for multielemental analysis with a mercury(II) preconcentration step using a resin Chelite-S(R)(Serva Feinbiochemica Heidelberg, Part No. 41709) packed minicolumn by inductively coupled plasma atomic emission spectroscopy is described. A mercury reductive elution procedure with a mixture of SnCl2/HCl was used, which allows use of 6 mol/L HCl solution instead of concentrated hydrochoric acid. The main parameters related to ICP operation, such as radio frequency power (950-1750 W), auxiliary argon flow (0.0-1.5 L/min) and spray chamber nebulizer pressure (15-35 psi), were studied. Optimization of the FIA system was reached by defining the best eluent carrier stream (1.4-2.8 mL/min), Hgdegrees carrier stream (10-40 mL min(-1)), loading time (0.5-4.0 min), sample flow rate (1.25-10.0 mL/min), temperature of reactor gas liquid separator (GLS) (25-75 degreesC) and eluent volume (50-350 muL). Throughput is around 30 samples per hour for analytical solutions within the range 50-2500 ng Hg(II)/L. Results from certified material showed good precision (RSD < 3%, n = 12) and no statistical difference was observed for real samples analyzed by AAS and by the proposed system.
Keywords: multielemental analysis; Chelite (R) S resin; FIA; cold vapor-ICP-AES